Peningkatan Motivasi dan Minat Belajar pada Pembelajaran PAI Siswa yang Berperilaku Off-Task di kelas X1 A Madrasah Aliyah Raudhatul 'Ulum dengan Metode Produk Kreatif : Peningkatan Motivasi dan Minat Belajar siswa yang Berperilaku Off-Task - Tonang Saima; Siti Ruslina; Syari’ah; Uji Istiqomah (Idarotuna: Jurnal Manajemen Pendidikan Islam, 2025)
Off-task behavior among students often becomes a challenge in the learning process, particularly in Islamic Education (PAI), which requires active participation and deep understanding. This study aims to examine the effectiveness of the creative product method in improving the motivation and learning interest of Grade XI A students at Madrasah Aliyah (MA) Raudhatul ‘Ulum who tend to display off-task behavior. The research employed a quasiexperimental design using a pre-test post-test control group model, allowing comparison between the experimental and control groups. Instruments used in this study included tests, questionnaires, and observations to measure changes in students’ motivation, interest, and engagement during the learning process. The findings reveal that the application of the creative product method encourages students to participate more actively, express their understanding through innovative works, and reduce irrelevant behaviors during lessons. These results highlight that the creative product method not only enhances students’ motivation and learning interest but also contributes to fostering a positive attitude toward Islamic Education among Grade XI A students at MA Raudhatul ‘Ulum.